Case Writing And Analysis: Silver Bird Group Berhad A Strategic Business Plan - Hooi, Long See (2004)
The central theme of this case analysis is the formulation of a Strategic Business Plan for a public listed entity involved in the production and distribution of food products. The study and analysis of the Silver Bird Group Berhad using systematic business tools will assist in the formulation of practical business and corporate level strategies to not only strengthen itself against the onslaught of competitors' aggressive movement but also enhance the Group's competitive structure to continue its remarkable performance in the next 5 years.